A first approach to a neuropsychological screening tool using eye-tracking for bedside cognitive testing based on the Edinburgh Cognitive and Behavioural ALS Screen. Issue 5 (3rd July 2017) - Keller, Jürgen; Krimly, Amon; Bauer, Lisa; Schulenburg, Sarah; Böhm, Sarah; Aho-Özhan, Helena E. A.; Uttner, Ingo; Gorges, Martin; Kassubek, Jan; Pinkhardt, Elmar H.; Abrahams, Sharon; Ludolph, Albert C.; et al.
Abstract: Objective : Reliable assessment of cognitive functions is a challenging task in amyotrophic lateral sclerosis (ALS) patients unable to speak and write. We therefore present an eye-tracking based neuropsychological screening tool based on the Edinburgh Cognitive and Behavioural ALS Screen (ECAS), a standard screening tool for cognitive deficits in ALS. Methods : In total, 46 ALS patients and 50 healthy controls matched for age, gender and education were tested with an oculomotor based and a standard paper-and-pencil version of the ECAS. Results : Significant correlation between both versions was observed for ALS patients and healthy controls in the ECAS total score and in all of its ALS-specific domains (all r > 0.3; all p < 0.05). The eye-tracking version of the ECAS reliably distinguished between ALS patients and healthy controls in the ECAS total score ( p < 0.05). Also, cognitively impaired and non-impaired patients could be reliably distinguished with a specificity of 95%. Conclusion : This study provides first evidence that the eye-tracking based ECAS version is a promising approach for assessing cognitive deficits in ALS patients who are unable to speak or write.